What's Constitutional about Revolutions?. (20th January 2022) - Arban, Erika; Samararatne, Dinesha
Abstract: Theorists have flirted with the idea of revolution for quite some time, mainly exploring the political, social and constitutional implications of this idea. Revolutions are easily associated with images of violent upsurges, social unrest and overturning of ruling leaders. However, there is a close link between revolutions and constitutionalism more generally: in fact, a revolution is often followed by a new constitutional moment, and the idea of 'revolution' has even been used in the context of judicial decision making. In theoretical terms, the intersection between constitutions, constitutionalism and revolution has emerged as a theme in academic legal scholarship in the past few years. 1 In this review article, we engage with one of the latest publications in this area, Constitutional Revolution by Jacobsohn and Roznai whose purpose is to offer a theoretical and comparative account of the concept of revolution as applied in/to constitutional law. The article is structured as follows. First, we consider the central claim made in the book, and then comment on some of the methodological choices made by the authors. Next, we situate the book within the broader scholarship on revolutions, exploring the resurgence of the idea of (constitutional) revolutions as unfolded in the social sciences. We then try to 'recast' the concept of revolution in constitutional theory by exploring the analytical value of the theorisation and some limits to its application, reflecting on some of the tensions that emerge from such conceptualisation. Finally, we test the theory through the constitutional experiences of two jurisdictions not considered in the book: Sri Lanka and Italy.